Oil Palm Leaves as an In-situ Bio-silica Source in Sustainable Synthesis of V2O5-SiO2 - Yudha S., Salprima; Adfa, Morina; Wibowo, Risky Hadi; Reagen, Muhamad Alvin (Science and Technology Indonesia, 2025)
Using ammonium vanadate and natural silica from oil palm leaves in situ at 900oC is a sustainable synthesis method for producing V2O5-SiO2 mixed oxides in the form of a brownish powder. Therefore, this study aims to investigate a more environmentally friendly alternative to synthesizing V2O5-SiO2 using oil palm leaves, a by-product from oil palm farming. The XRD analysis of the reaction products showed specific V2O5 peaks and broadened peaks, indicating the presence of amorphous silica. The Fourier transform infrared (FTIR) analysis, which revealed the presence of Si-O-Si and Si-O-V functional groups, also supported the characteristic assessment. In addition, X-ray fluorescence (XRF) analysis showed that V2O5 (46.70 mass%) and SiO2 (52.60 mass%) were present, along with small amounts of other possible metal oxides, such as P2O5, K2O, CaO, Fe2O3, Al2O3, and PdO.